(untitled) (Global Journals of Research in Engineering, 2025)
This study attempts to present and highlight through their theatricality the historical processions parades and anniversaries of remembrance in the early 20th century that took place respectively in the natural environment of cities in Greece and Australia Inspired by the ideals of the state the principles of democracy but also the evolutionary reflexive dynamics of the correlation of space with the urban environment the grand Assemblies reflected and underlined important historical turning points strengthening the spirit of the populations in the early 20th century Ultimately as it turns out the earth marches in parallel steps and the setting of the cities of Athens and Thessaloniki and the megacities of Melbourne and Sydney significantly influenced and emotionally charged the great celebrations